IMPLEMENTASI BUKU PEDOMAN PENERIMAAN KOMUNI PERTAMA KEUSKUPAN SURABAYA - Paskalia, Elisa Maria; Ardijanto, Don Bosco Karnan (CREDENDUM: Jurnal Pendidikan Agama, 2020)
This research aims to describe the candidates for First Communion, the content of the Guidelines for Receiving First Communion published by the Diocese of Surabaya, and the implementation of these guidelines in St. Cornelius Parish, Madiun. The study employs a qualitative research method with a purposive sampling technique to select Informants. Data collection was conducted through interviews. The research was carried out at St. Cornelius Parish, Madiun, within a specified period. The findings reveal three key conclusions: First, the candidates for First Communion are baptized Catholics who have received sufficient knowledge and preparation. Second, the Guidelines for Receiving First Communion include the meaning of the Eucharist, the profile of First Communion candidates, the objectives of preparation, and practical aspects. Third, St. Cornelius Parish, Madiun, has implemented these guidelines as the primary reference for First Communion preparation.